2020
DOI: 10.1155/2020/1484321
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1/GLP-1R Signaling Regulates Ovarian PCOS-Associated Granulosa Cells Proliferation and Antiapoptosis by Modification of Forkhead Box Protein O1 Phosphorylation Sites

Abstract: As the major cause of female anovulatory infertility, polycystic ovary syndrome (PCOS) affects a great proportion of women at childbearing age. Although glucagon-like peptide 1 receptor agonists (GLP-IRAs) show therapeutic effects for PCOS, its target and underlying mechanism remains elusive. In the present study, we identified that, both in vivo and in vitro, GLP-1 functioned as the regulator of proliferation and antiapoptosis of MGCs of follicle in PCOS mouse ovary. Furthermore, forkhead box protein O1 (FoxO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…After 6 weeks, liraglutide induced granulosa cell proliferation and promoted their viability in DHEA-induced PCOS mice by modifying the forkhead box protein O1 (FOXO1) phosphorylation site. 62 In another study of 20 Parkes strain mice, PCOS was induced using DHEA at a dose of 6 mg/100 g of body weight per day. The PCOS-induced mice then received liraglutide, either 100 or 200 µg/day twice a day for 14 days.…”
Section: Evidence For the Therapeutic Potentials Of Glp-1 Ra In Pcosmentioning
confidence: 99%
“…After 6 weeks, liraglutide induced granulosa cell proliferation and promoted their viability in DHEA-induced PCOS mice by modifying the forkhead box protein O1 (FOXO1) phosphorylation site. 62 In another study of 20 Parkes strain mice, PCOS was induced using DHEA at a dose of 6 mg/100 g of body weight per day. The PCOS-induced mice then received liraglutide, either 100 or 200 µg/day twice a day for 14 days.…”
Section: Evidence For the Therapeutic Potentials Of Glp-1 Ra In Pcosmentioning
confidence: 99%
“…Indeed, we found that both GIP and GLP-1 receptors were present in the ovaries and uterine horn, suggesting their involvement in important aspects of female reproductive function. Previous studies have also demonstrated GLP-1Rs in mouse ovarian granulosa cells [ 39 ].…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have suggested that the proliferation and apoptosis of granulosa cells (GCs) are the root causes of follicular development and atresia, with forkhead box protein O1 (FoxO1) playing an important role in promoting PCOS follicular atresia and GCs apoptosis ( 162 , 163 ). The GLP-1/GLP-1R axis was demonstrated to enhance the activity of PCOS ovarian granulosa cells by partially modifying the FoxO1 phosphorylation sites, thereby promoting oocyte maturation ( 164 ). In addition, liraglutide was found to repair the cognitive impairment in a rat model of PCOS by inhibiting the overexpression of the Notch signaling pathway ( 165 ).…”
Section: Effects On Polycystic Ovary Syndromementioning
confidence: 99%